TEACHING THE PRONUNCIATION OF DIGRAPH SOUND SH /ʃ/ USING TONGUE TWISTETS TO FIRST GRADE STUDENTS - Novita Teka Sari; Luwandi Suhartono; Wardah Wardah (Universitas Tanjungpura, 2022)
This research aims at finding out how effective Tongue Twister is in helping the first graders of Immanuel Bilingual Class Pontianak in the academic year of 2016-2017 learn to pronounce digraph sound ‘sh’ /∫/. There were 32 participants of this research. The data collecting method that the researcher used was qualitative data. As for the instruments used were spoken test (oral performance test). There were three phases that the researcher underwent to collect the data for the research. The first phase was the pre-test, which then was followed by the treatments, and then as the last phase post-test was given. The treatments were given in three consecutive days. Each treatment was given in 35-minute duration. From the data calculation and analysis, the mean score for the pre-test was 3.98 meanwhile the post-test was 7.85. Thus, the students’ pronunciation was improved by 3.87 points or 32.71%. Based on the result, it can be concluded that teaching pronunciation using Tongue Twister was well-accepted by the students and has significantly improved their pronunciation of digraph sound ‘sh’ /∫/. Hopefully this finding can be used as a reference when the intention of a research is to find the appropriate treatment to conduct in teaching pronunciation.